Green-synthesized gold nanoparticles from black tea extract enhance the chemosensitivity of doxorubicin in HCT116 cells via a ROS-dependent pathway. Issue 15 (23rd March 2022) - Das, Tanushree; Mishra, Snehasis; Nag, Sayoni; Saha, Krishna Das
Abstract : Green gold nanoparticles (GNPs) were prepared from black tea extract (BTE) and used to examine the chemosensitivity of doxorubicin in colon cancer cell line HCT116. Abstract : Green gold nanoparticles (GNPs) were prepared from black tea extract (BTE) and used to examine the chemosensitivity of doxorubicin in colon cancer cell line HCT116. BTE-GNPs were prepared by a single-step method and characterized by UV-Vis spectroscopy, FTIR spectroscopy, SEM, DLS and zeta-potential. The MTT assay was performed to determine the cytotoxicity of HCT116 cells and also normal kidney cells HEK293. Apoptosis and ROS generation were investigated by flow cytometry. The inhibition of ROS levels by the inhibitor NAC was determined by both spectrofluorimetry and confocal microscopy. Expression levels of pro- and anti-apoptotic proteins were determined by a western blot technique. BTE-GNPs significantly enhanced the cytotoxic effect of DOX with its co-treatment in HCT116 cells. The cytotoxic effect of BTE-GNP + DOX was involved in apoptosis via a ROS-dependent pathway by enhancing the pro-apoptotic protein expression. Therefore, our results indicated that green gold nanoparticles of black tea extract (BTE-GNP) may be potent chemosensitizers of doxorubicin.